2021
DOI: 10.1111/brv.12784
|View full text |Cite
|
Sign up to set email alerts
|

The thermal environment as a moderator of social evolution

Abstract: Animal sociality plays a crucial organisational role in evolution. As a result, understanding the factors that promote the emergence, maintenance, and diversification of animal societies is of great interest to biologists. Climate is among the foremost ecological factors implicated in evolutionary transitions in social organisation, but we are only beginning to unravel the possible mechanisms and specific climatic variables that underlie these associations. Ambient temperature is a key abiotic factor shaping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 288 publications
(328 reference statements)
0
11
0
Order By: Relevance
“…A recent review by Moss and While ( 2021 ) concluded that ‘we lack empirical evidence that explicitly tests the effects of temperature on social behaviour’. Here, we provide evidence for a causal effect of rearing temperature on social behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent review by Moss and While ( 2021 ) concluded that ‘we lack empirical evidence that explicitly tests the effects of temperature on social behaviour’. Here, we provide evidence for a causal effect of rearing temperature on social behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we still saw reduced sociability in fish reared at a higher temperature over two generations, regardless of their thermal habitat of origin (Figure 5 ). This suggests that the effects of temperature on sociability are at least partially mediated through intrinsic pathways, such as physiological or endocrine changes that occur throughout development (Moss & While, 2021 ), although it is worth noting that we also cannot eliminate the possible contribution of parental and other epigenetic effects from the F1 generation (Fuxjäger et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations